(untitled) (Research, Society and Development, 2022)
In the global mobilization, surveillance agencies and society are together in facing the pandemic, with the nursing professionals who work on the front line of the pandemic in health services, at the beginning it was realized that little was known about the disease, its form of prevention, pathogenesis or treatment. Nursing is in the treatment of Covid-19 cases and faces serious implications for their working conditions and personal safety to be recognized. The specific objective was to show what were the changes of Covid-19 in nursing. The methodology used was a bibliographic review in the Google Scholar database, VHL and SciELO, published between 2020 and 2022, available in full. 5 articles from the SciELO and Google academic databases were included, in the VHL there were only 11 scientific articles, which resulted in a final sample of 21 scientific articles from different journals. two categories according to their theme, which were: Category A - Present the main impacts of Covid-19 on nursing; Category B - Show what were the changes of Covid-19 in nursing. The main impacts The lack of sufficient PPE had an adverse impact on nursing performance, which exacerbated the shortage of manpower. Covid-19 has brought many changes over the last few years, although we have all adapted to these changes on a day-to-day basis, the healthcare market has also had to adapt quickly. The coronavirus has changed nursing not only for those already working in the field, but also for nursing students. The pandemic has exposed underlying issues and created new issues in recruitment, educational readiness, retention, well-being, understanding of workforce migration.